Case Report: Fatal case of dual infection Metapneumovirus complicated by Streptococcus pyogenes - Krivonos, Danil; Pavlenko, Alexander; Lukina-Gronskaya, Alexandra; Korneenko, Elena; Speranskaya, Anna; Ilina, Elena (Frontiers in Medicine, 2025)
Human Metapneumovirus (hMPV) is a common cause of acute respiratory viral infection in humans, typically occurring in children and causing no serious complications. However, the severity of the disease can be exacerbated by certain bacterial pathogens that lead to severe illness and even death. This report details a fulminant case of dual infection with hMPV and group A Streptococcus (Streptococcus pyogenes) in a three-year-old child. The whole genome sequencing of isolated clinical S. pyogenes strains was conducted, followed by an analysis of the genomic characteristics of the pathogen. Also, potential viral and bacterial pathogens were identified by qPCR and 16S rRNA metagenomic sequencing in any autopsy materials obtained from the patient. Children who had contact with the patient and began to exhibit symptoms of a cold were also tested and confirmed to have uncomplicated hMPV infection. The S. pyogenes strain has been found to contain five genes for various streptococcal exotoxins (speA, speB, speJ, speG and smeZ). In addition, the speA gene is situated in close proximity to the prophage, which may suggest that it is encoded and transferred specifically by the bacteriophage. We hypothesize that it was the cumulative effects of different streptococcal exotoxins that led to the patient’s death.